AUTOMATED RETINAL LAYER SEGMENTATION AND THEIR THICKNESS PROFILES IN HEALTHY SUBJECTS: A Comparison of 55° Wide-field and Conventional 30° Spectral Domain-Optical Coherence Tomography. Issue 10 (October 2020) - Giannakaki-Zimmermann, Helena; Munk, Marion R.; Ebneter, Andreas; Wolf, Sebastian; Zinkernagel, Martin
Abstract : Purpose: To assess whether retinal thickness measurements with a standard 30° spectral domain optical coherence tomography (SD-OCT) are comparable with wide-field 55° SD-OCT. Methods: Thirty-three healthy individuals were scanned using 55° as well as 30° SD-OCT according to a standardized protocol. Automated retinal layer segmentation of standard and wide-field SD-OCTs was assessed using customized software. Results: Both lenses showed a high correlation when analyzing total retinal thickness within the central, the inner, and the outer retinal ring (r = > 0.9). Automated thickness measurements with the 55° system were marginally higher compared with the 30° lens. The thickness of each separate retinal layer using automated segmentation showed excellent correlations within the inner and outer rings (range: r = 0.6—r = 0.9 for the inner ring and range: r = 0.9—r = 1.0 for the outer ring). Conclusion: Fifty-five degree wide-field SD-OCT provides a good overview of the posterior pole and presents similar quantitative values as a standard 30° OCT lens. Therefore, thickness values are comparable when switching between these two lenses. Abstract : Fifty-five degree wide-field spectral domain optical coherence tomography provides an alternative to standard 30° optical coherence tomography lens with comparable thickness values with a greater field of view.